2008
DOI: 10.1128/jcm.00490-08
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, Novel, Specific, High-Throughput Assay for Diagnosis of Loa loa Infection

Abstract: The ability to diagnose Loa loa infection readily and accurately remains a demanding task. Among the available diagnostic methods, many are impractical for point-of-care field testing. To investigate whether luciferase immunoprecipitation systems (LIPS) can be used for rapid and specific diagnosis of L. loa infection, a LIPS assay was developed based on immunoglobulin G (IgG) and IgG4 subclass antibodies to a recombinant L. loa SXP-1 (designated LlSXP-1) antigen and tested with sera from healthy controls or pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 22 publications
4
64
0
1
Order By: Relevance
“…In this study, we confirmed the results of previous studies that the recombinant-antigen-based LIPS assay accurately differentiates between sera from patients with parasitologically proven S. stercoralis infection and healthy, uninfected controls, compared to the current best available serologic test (21). LIPS assays have been successfully applied to the characterization of antibody responses to multiple infections, including Pneumocystis jirovecii, HIV, hepatitis virus, and Loa loa and, more recently, to the diagnosis of infections due to S. stercoralis (4,6,21). As has been shown previously, the LIPS format was additionally found to be superior to an ELISAbased format using the same NIE recombinant antigen (21).…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we confirmed the results of previous studies that the recombinant-antigen-based LIPS assay accurately differentiates between sera from patients with parasitologically proven S. stercoralis infection and healthy, uninfected controls, compared to the current best available serologic test (21). LIPS assays have been successfully applied to the characterization of antibody responses to multiple infections, including Pneumocystis jirovecii, HIV, hepatitis virus, and Loa loa and, more recently, to the diagnosis of infections due to S. stercoralis (4,6,21). As has been shown previously, the LIPS format was additionally found to be superior to an ELISAbased format using the same NIE recombinant antigen (21).…”
Section: Discussionsupporting
confidence: 87%
“…While the HSV-1 and HSV-2 ICP8 antigens used in the LIPS assay are highly conserved (89% amino acid identity), there were marked quantitative differences to these antigens in the plasma samples tested. This strain specificity is reminiscent of the reduced LIPS serologic responses to related filarial antigens in subjects infected with related worms (12,28).…”
Section: Discussionmentioning
confidence: 93%
“…Recently, we showed that luciferase immunoprecipitation system (LIPS) assays can quantitatively measure antibody responses to cancer-associated autoantigens (8), autoantigens associated with autoimmune diseases (9,10), and a variety of infectious agents, including hepatitis C virus, human immunodeficiency virus (HIV) (7), human T-cell leukemia virus type 1 (11), and filaria (12,28). These assays measure antibody levels in immunoprecipitations by using fusion proteins consisting of Renilla luciferase (Ruc)-antigen produced in Cos1 cells.…”
mentioning
confidence: 99%
“…A method known as luciferase immunoprecipitation systems (LIPS) quantitatively measures antibodies to a wide range of infectious agents, [16][17][18][19] as well as to a variety of human autoantigens. [20][21][22] LIPS is a liquid phase immunoassay that uses antigens directly tagged with Renilla luciferase, which can sensitively and quantitatively detect antibodies.…”
Section: Functional Testing Proved That Autoantibodies Directed Againmentioning
confidence: 99%